Pengaruh Hatha Yoga Terhadap Perilaku Bullying Pada Siswa Kelas III SD No. 2 Sibanggede - Juniartha, Made G.; Suputra, I Kadek Darmo; Putri , Ni Luh Santhi Icaka (Jurnal Penelitian Agama Hindu, 2025)
Bullying occurred among third-grade students at SD No. 2 Sibanggede. Students identified as perpetrators exhibited high levels of aggressiveness, while those identified as victims demonstrated low social and emotional skills. Hatha yoga incorporates various techniques such as asana, pranayama, kriya, mudra, and bandha, which can be utilized to enhance emotional regulation and reduce aggressiveness. The purpose of this study was to investigate the effect of hatha yoga on bullying behavior among third-grade students at SD No. 2 Sibanggede. This research employed an experimental method with a one-group pretest-posttest design. The population consisted of all 21 third-grade students at SD No. 2 Sibanggede. The sampling technique used was total sampling, in which the entire population was included as the sample. Data were collected using the self-report method through the Olweus Bully/Victim Questionnaire (OBVQ), which includes separate questionnaires for bullying perpetrators and victims. This instrument has a Cronbach's alpha reliability coefficient of 0.87 for the perpetrator questionnaire and 0.85 for the victim questionnaire. Data analysis was conducted using the Wilcoxon test. The results showed a Z value of -2.733 with a significance level of 0.006 (p < 0.05). These findings indicate that hatha yoga has an effect on bullying behavior exhibited by perpetrators among third-grade students at SD No. 2 Sibanggede. Hatha yoga was also reported to reduce the bullying experienced by victims, although the reduction was not statistically significant.